The anterior cingulate cortex as a key locus of ketamine's antidepressant action. (August 2021) - Alexander, Laith; Jelen, Luke A.; Mehta, Mitul A.; Young, Allan H.
Highlights: Ketamine modulates anterior cingulate cortex (ACC) activity over minutes and hours. Changes in ACC activity correlate with ketamine's antidepressant effects. Ketamine's effects on anhedonia depend on modulation of dorsal and subgenual ACC. Ketamine's action on ACC may reduce emotional pain and rumination. Rodent and non-human primate studies are key to understanding ketamine's effects. Abstract: The subdivisions of the anterior cingulate cortex (ACC) – including subgenual, perigenual and dorsal zones – are implicated in the etiology, pathogenesis and treatment of major depression. We review an emerging body of evidence which suggests that changes in ACC activity are critically important in mediating the antidepressant effects of ketamine, the prototypical member of an emerging class of rapidly acting antidepressants. Infusions of ketamine induce acute (over minutes) and post-acute (over hours to days) modulations in subgenual and perigenual activity, and importantly, these changes can correlate with antidepressant efficacy. The subgenual and dorsal zones of the ACC have been specifically implicated in ketamine's anti-anhedonic effects. We emphasize the synergistic relationship between neuroimaging studies in humans and brain manipulations in animals to understand the causal relationship between changes in brain activity and therapeutic efficacy. We conclude with circuit-based perspectives on ketamine's action: first, related to ACC function in a central network mediating affective pain, and second, related to its role as the anterior node of the default mode network.